Dinamika Persepsi Sosial Habaib Baalwi Nusantara: Telaah Edukatif Legitimasi Keturunan Nabi Pada Sosial-Keagamaan Kontemporer Indonesia - Moh Muntholib (Jurnal Al-Fatih, 2026)
This study aims to analyze the changing public perception of the Baalwi clan's habaib as descendants of the Prophet Muhammad SAW in the Indonesian archipelago and to identify the factors that have led to the decline of this reputation in the contemporary socio-religious context. This study uses a descriptive qualitative approach with literature study and media analysis methods, through data collection from relevant scientific journals, books, articles, and digital sources, which are then analyzed critically and comprehensively. The results show that the decline of this reputation is influenced by several main factors, namely the emergence of criticism of the validity of lineage, the practice of exploiting genealogical identity in social structures, the development of information technology that expands public access to critical discourse, and increasing moral expectations of religious figures. These factors encourage a change in public mindset from one that was initially dogmatically accepting to being more rational and selective in assessing religious authority. This study concludes that religious legitimacy in the modern era is no longer based solely on lineage, but on the quality of knowledge, moral integrity, and real contributions to social life. Therefore, it is necessary to strengthen Islamic education that is more critical, objective, and based on substantial values in responding to these dynamics.